It matters how you start: Early numeracy mastery predicts high school math course‐taking and college attendance. Issue 2 (26th November 2021) - Davis‐Kean, Pamela E.; Domina, Thurston; Kuhfeld, Megan; Ellis, Alexa; Gershoff, Elizabeth T.
Abstract: Using data from the Applied Problems subtest of the Woodcock‐Johnson Tests of Achievement (Woodcock & Johnson, 1989/1990, Woodcock‐Johnson psycho‐educational battery‐revised. Allen, TX: DLM Teaching Resources ) administered to 1, 364 children from the National Institute of Child Health and Human Development (NICHD) Study of Early Childcare and Youth Development (SECCYD), this study measures children's mastery of three numeric competencies (counting, concrete representational arithmetic and abstract arithmetic operations) at 54 months of age. We find that, even after controlling for key demographic characteristics, the numeric competency that children master prior to school entry relates to important educational transitions in secondary and post‐secondary education. Those children who showed low numeric competency prior to school entry enrolled in lower math track classes in high school and were less likely to enrol in college. Important numeracy competency differences at age 54 months related to socioeconomic inequalities were also found. These findings suggest that important indicators of long‐term schooling success (i.e., advanced math courses, college enrollment) are evident prior to schooling based on the levels of numeracy mastery.